Effectiveness-Supporting Methods, Strengthening the Soft-Skills and Communication Competences - Váradi-Csema, Erika (Interdisciplinary and Child-Friendly Communication, 2025)
Strengthening the communication competencies of professionals who come into contact with children, and a wider knowledge of children’s individual needs and age characteristics is an important prerequisite for the fuller enforcement of children’s rights. The declaration and guaranteeing of children’s rights is an important prerequisite at the level of legal regulation affecting different areas of law, but their actual practical implementation depends on the knowledge of the professionals with whom the affected age group comes into contact. Recognising this is an important step forward at both international and national level. This will not only mean greater protection for children and wider recognition of their specific needs but will also make cooperation between relevant professionals and institutions more effective. Therefore, complex training programs are important in all relevant fields, which aim to develop ‘soft-skills’ such as communication, problem-solving or the ability to cooperate in addition to ‘hard-skills’.Keywords: communication competences, soft-skills, child-friendly communication, general key competence in justice system, speech, language and communication needs (SLCN), system-abuse, institutional violence